Obesity and Oxidative Stress: Potential Roles of Melatonin as Antioxidant and Metabolic Regulator - Bonnefont-Rousselot, Dominique (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Obesity is associated with an oxidative stress status, defined as an excessive production of reactive oxygen species (ROS) compared to the level of antioxidants acting in the natural defence systems. Several sources of ROS can be identified in obesity (e.g., mitochondrial respiratory chain, or NADPH oxidase) and could contribute to the pathogenesis of obesity. Indeed, these conditions favour the development of insulin resistance and metabolic syndrome through deregulation of adipokines and pro-inflammatory cytokines, so that it could be of interest to associate antioxidant therapeutic strategies with strategies of weight loss. Among antioxidants, melatonin holds a special place, on the one hand for its antioxidant and anti-inflammatory properties, and on the other hand for its role as a metabolic regulator. As melatonin modulates several processes involved in obesity and its related metabolic alterations, it could have a therapeutic interest in the treatment of obesity.
Keywords: melatonin